Analysis of technologies for restoring the serviceability of reinforced concrete ceiling structures - MOLODID, Oleksandr; PLOKHUTA, Ruslana; MOLODID, Olena; MUSIIAKA, Ivan (Ways to Improve Construction Efficiency, 2024)
As a result of military operations, a significant part of construction objects was damaged by off-design impacts. Among the damaged structures, a significant proportion is accounted for ceiling. In our case, majority of ceilings are made of hollow-core reinforced concrete slabs. According to the current regulatory documents, some of these ceilings are subject to restoration. Therefore, the analysis and identification of the most rational and effective technologies for restoring the operational suitability of damaged building structures, in particular, ceilings, is an urgent task today. The article analyzes the known classical and new technologies for repairing and strengthening reinforced concrete slabs, including: dismantling damaged slab and following production of the plate in-place; applying cement-based repair mortars; repairing with epoxy materials; strengthening structures with carbon or basalt materials; classical technologies (bringing metal unloading beams from above (below), installing double-cantilever unloading beams, installing tie bars, creating indistinguishability of beams, building up the beams, etc.). The advantages and disadvantages of each of the technologies, both structural and technological, were identified. The analysis shows that the existing methods are aimed either at repairing damage or at strengthening defect-free structures. Therefore, the development of new or improvement of known technologies for the comprehensive restoration of hollow core slabs is an urgent task. However, taking into account the types of damage to hollow-core slabs as a result of off-design impacts, a new or improved technology for their comprehensive restoration is currently needed. At the same time, such a technology should be structurally and technologically reasoned.